Antimicrobial Properties of Green Biomaterials - Flora B.; Singh A.K.; Kumar R.; Balakrishnan K.; Singh A.; Gupta P.K. (My University, 2025)
Green biomaterials originate from natural and sustainable resources, frequently encouraging eco-friendly choices and minimizing environmental adverse impacts. Various green biomaterials possess inherent or enhanced antibacterial properties, making them highly valuable for various applications. Biomaterials have transformed both therapeutic and preventive healthcare. This has accelerated the development of scaffolds for tissue engineering, drug delivery systems, and implants with enhanced functionality. However, several strategies have been employed to utilize natural biomaterials that exhibit antimicrobial qualities in either form or design to avoid the infection linked to the use of biomedical implants and devices as well as boost the wound healing process. This chapter has covered the demand for green biomaterials with antimicrobial properties and their applications in various sectors. However, the factors influencing antimicrobial activity, and the assays used to measure it have been documented. Nevertheless, there has also been a discussion of the various structural configurations of green biomaterials exhibiting antibacterial activity. © 2025 American Chemical Society.